2021
DOI: 10.5194/acp-2021-373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Four years of global carbon cycle observed from OCO-2 version 9 and in situ data, and comparison to OCO-2 v7

Abstract: Abstract. The Orbiting Carbon Observatory 2 (OCO-2) satellite has been provided information to estimate carbon dioxide (CO2) fluxes at global and regional scales since 2014 through the combination of CO2 retrievals with top-down atmospheric inversion methods. Column average CO2 dry air mole fraction retrievals has been constantly improved. A bias correction has been applied in the OCO-2 version 9 retrievals compared to the previous OCO-2 version 7r improving data accuracy and coverage. We study an ensemble of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
(120 reference statements)
1
15
0
Order By: Relevance
“…ObsPack presents calibrated CO 2 measurements from different observing platforms, such as surface flasks, tall towers, and aircrafts operated by numerous institutes in a common format. For this study, we applied ObsPack data derived for the OCO‐2 v9 MIP (Peiro et al., 2021). We assimilated ObsPack measurements which were flagged as “assimilable” by a prior run of NOAA’s CarbonTracker data assimilation system.…”
Section: Datamentioning
confidence: 99%
“…ObsPack presents calibrated CO 2 measurements from different observing platforms, such as surface flasks, tall towers, and aircrafts operated by numerous institutes in a common format. For this study, we applied ObsPack data derived for the OCO‐2 v9 MIP (Peiro et al., 2021). We assimilated ObsPack measurements which were flagged as “assimilable” by a prior run of NOAA’s CarbonTracker data assimilation system.…”
Section: Datamentioning
confidence: 99%
“…4). These global inversions are part of the OCO-2 Model Intercomparison Project (MIP) (Crowell et al, 2019;Peiro et al, 2021). In this study, we used the OCO-2 MIP flux version found in Peiro et al (2021).…”
Section: Global Atmospheric Inversionsmentioning
confidence: 99%
“…These global inversions are part of the OCO-2 Model Intercomparison Project (MIP) (Crowell et al, 2019;Peiro et al, 2021). In this study, we used the OCO-2 MIP flux version found in Peiro et al (2021). In Peiro et al (2021), the global inversions were performed using the assimilation OCO-2 (version…”
Section: Global Atmospheric Inversionsmentioning
confidence: 99%
See 2 more Smart Citations